Branding Thailand and its implication - Saenjai, Thidarat (KDI School, 2011)
Nation branding is becoming an important issue and interest for the academics, practitioners, business people, government officials, politicians and the public in various countries, particularly in the past decade. More and more countries are jumping on the bandwagon in order to change the world’s view of their nations in the attempt to increase their comparative advantage in the international arena. Thailand is no different. It is in the process of improving its image to attract the attention, respect and trust from the potential investors, visitors, governments, media and consumers of other nations. With this in mind, the government is projecting Thailand’s positive strengths to give it a comparative advantage in the global market place. This thesis investigates Thailand’s effort in trying to improve and broadening its recognition in the international arena by adopting the concepts of nation branding. It examines Thailand in relations to Simon Anholt’s competitive identity, which represents the six ‘natural’ channels of communication though which countries communicate with the world in order to create its successful brand and recognition: exports, governance, investment and immigration, culture and heritage, people and tourism. A qualitative approach of interviews, case studies and survey are used to research on how branding theory can be applied to Thailand. In spite of the complexity of the subject and the suggestion that most scholars and practitioners made that tourism is the one of the softer element of the comparative identities for a nation to use as a tool to brand the country, this study attempts to develop an appropriate framework to support that Thailand can brand itself using its strengths through tourism. Moreover, other relevant implications are discussed to address the need for a successful nation branding strategy for Thailand.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Thailand.